Methodology of The Research of Organizational and Economic Bases of Development of Agro, Ethno and Spiritual Tourism in the Republic of Kazakhstan - Saparbayev, Abdizhapar; Saparova, Gulnara; Makulova, Aiymzhan; Imatayeva, Aliya; Abdulkhalil, Aisha (E3S web of conferences, 2020)
The article discusses the problems and prospects for the development of ethno, eco, agro and spiritual tourism. An important problem of ethno-tourism is the problem of increasing the excursion attractiveness of countries and regions. The main environmental problem of the development of society is the protection and storage of natural identity and security. This work is the result of research conducted by the author for the period 2012-2017. using statistical and financial reporting of Kazakhstan tourism. The work includes methods for comparing current years and past (base).Purpose of scientific work is analysis of the trends of development and approaches to the development of the state programs of the development of agro-, Etna and spiritual tourism in the economy Of the Republic Kazakhstan. Lies in the fact that in further development of methodological base the estimation of the effectiveness of agro-, Etna and spiritual tourism on the basis of innovation approach and unity of the processes of their functioning. The methods proposed in this work show what methods of programs can be used for the development of tourism both within the state and abroad.